PERAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA PEGAWAI DI BALAI PENJAMINAN MUTU PENDIDIKAN (BPMP) SUMATERA UTARA MEDAN - Nina Amanda; Nur Ahmadi Bi Rahmani (Cahaya Ilmu Bangsa Institute, 2023)
Work motivation is an internal or external driver that encourages a person to achieve goals and optimal performance in the work environment. Based on the problems that have been presented, it is clear that the North Sumatra Education Quality Assurance Center has not been managed well. Problems like this should be addressed immediately and maximized so that in the future it can be as good as it should be. If this is resolved, it will certainly create a comfortable and conducive atmosphere so that employees can carry out their work responsibilities well and optimally. Effective work motivation is the key to a company's long-term success. By understanding and applying the principles of motivation, you can create a dynamic and productive work environment, ensuring employee well-being and sustainable growth.